Internal Governance Mechanisms: Evidence from Islamic Banks - Majdi Anwar Quttainah; Liem Gai Sin (AIBPM Publisher, 2018)
The impact of institutional corporate governance on the financial performance of Islamic banks, with a specific focus on Shari’ah Supervisory Boards and corporate boards. The findings of this study indicate that Islamic banks with Shari’ah Supervisory Boards outperform Islamic banks without such boards, as measured by return on assets (ROA), return on equity (ROE), asset growth (AG), and interest margins (IM). Further findings of this study indicate that the financial performances of Islamic banks with Shari’ah Supervisory Boards and corporate boards are influenced by several board characteristics, including the size of the board and the education of the board members. Moreover, Shari’ah Supervisory Boards provide tighter monitoring and control, as well as more advising and counseling, as compared with Islamic banks without Shari’ah Supervisory Boards. Later findings indicate that Shari’ah Supervisory Boards’ affiliations with international Islamic financial institutions motivate the positive relationship between the Shari’ah Supervisory Boards and Islamic bank performance. Overall, this study provides strong evidence that Shari’ah Supervisory Boards benefit shareholders by complementing corporate boards and thus mitigating agency problems and agency costs.